The Role of Article 25 Income Tax Installments in Liquidity Risk Mitigation and Corporate Taxpayer Compliance - Ayunda Paramesywari; Rudi Sanjaya; Nazar Restu Anugrah; Amanda Faruk Arahman (MJK PUBLISHER, 2026)
The Article 25 Income Tax (PPh Article 25) is a monthly installment mechanism designed to facilitate taxpayers in fulfilling their tax obligations progressively throughout the fiscal year. This study analyzes the Article 25 Income Tax installment mechanism, its role in mitigating corporate liquidity risk, and its contribution to improving corporate taxpayer compliance. A qualitative descriptive approach was employed through a library research method by reviewing scholarly articles, reference books, and relevant tax regulations. The findings indicate that Article 25 Income Tax effectively supports liquidity management by distributing tax payments more proportionally, reducing cash flow risks, and providing installment flexibility during periods of declining business performance. In addition, this mechanism enhances corporate taxpayer compliance through a more structured payment system supported by the digitalization of tax administration. The novelty of this study lies in integrating liquidity management and tax compliance perspectives, demonstrating that optimizing Article 25 Income Tax contributes to corporate financial stability while supporting the sustainability of government tax revenue.